ANALYSIS OF TOOLS FOR MEASURING PROFESSIONAL COMPETENCES OF GRADUATES IN THE DIRECTION OF ICT TRAINING - Abdiyev, К.С.; Zhassandykyzy, М.; Maintcer, Д.А.; Naumenko, В.В.; Primbetova, Г.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article presents an analysis of the tasks used in the qualification exams in Kazakhstan and Russia. The analysis showed that in the CIS countries, qualification exams are held in the form of final certification after graduation. There are no additional certification exams for future IT specialists. The content of the test tasks used in the final certification is aimed at checking the assimilation of the educational materials of the studied disciplines by graduates, that is, compliance with the requirements of general educational standards. Whereas, in addition to general educational standards, when developing educational programs, both the Russian Federation and the Republic of Kazakhstan are guided by professional standards. Based on the results of the work, a problem was identified - the compliance of the skills and abilities of future specialists with the requirements of professional standards is not assessed. Consequently, employers do not have the opportunity to check the readiness of young specialists to perform specific work functions when hiring.